1990
DOI: 10.1055/s-2008-1071482
|View full text |Cite
|
Sign up to set email alerts
|

CSF Anomalies in Children Affected by Epilepsia Partialis Continua (EPC)

Abstract: In two children affected with "Epilepsia Partialis Continua" (EPC) of progressive type, probably secondary to a slow encephalitis, the percentage of T-lymphocytes in CSF was lower than normal (30% compared to 90%). The CSF-T-lymphocytes are characterized by their ability to form E-rosettes. In one patient signs of intrathecal synthesis of IgG, especially oligoclonal bands at isoelectrofocusing, were observed. These results confirm, that in this type of EPC some immunological parameters in the CSF are impaired;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…So far, the presence of antibody synthesis in the CSF compartment has not been studied systematically, and the finding of OBs in the CSF of patients with epilepsy is limited to single cases in the literature [23,24]. In our present work, intrathecal immunoglobulin synthesis was determined by oligoclonal IgG bands and IgM/IgA antibody serum/CSF indices, and was present in 34.1% of all patients with epilepsy.…”
Section: Discussionmentioning
confidence: 57%
“…So far, the presence of antibody synthesis in the CSF compartment has not been studied systematically, and the finding of OBs in the CSF of patients with epilepsy is limited to single cases in the literature [23,24]. In our present work, intrathecal immunoglobulin synthesis was determined by oligoclonal IgG bands and IgM/IgA antibody serum/CSF indices, and was present in 34.1% of all patients with epilepsy.…”
Section: Discussionmentioning
confidence: 57%
“…Rasmussen encephalitis is the prototype of epileptic syndromes in which an immunopathogenesis is presumed, and reported favorable responses to immunomodulatory treatment support this hypothesis (reviewed in Billiau et al, 2005; Vezzani and Granata, 2005). Our Rasmussen patient showed high‐titer antinuclear antibodies, elevated total IgG and intrathecal oligoclonal Ig synthesis, which have previously been described (Andrews et al, 1990; Gaggero et al, 1990), but failed to respond and experienced the typical dramatic deterioration (Oguni et al, 1991). Some authors have reported that the clinical success rate of IVIG was higher in patients with IgA or IgG2 deficiency, although many other studies have refuted these associations (Ariizumi et al, 1983; Duse et al, 1986; Rijckevorsel‐Harmant et al, 1986; van Rijckevorsel‐Harmant and Delire, 1988; Spina et al, 1989; Illum et al, 1990; Sterio et al, 1990; Echenne et al, 1991; Rijckevorsel‐Harmant et al, 1994; van Engelen et al, 1994d).…”
Section: Discussionmentioning
confidence: 99%